2021
DOI: 10.1159/000512085
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes of Split-Thickness Skin Grafts for Floor of Mouth Cancer Reconstruction

Abstract: <b><i>Introduction:</i></b> Patient-reported outcome measures (PROM) on quality of life (QOL) for early-stage floor of mouth carcinoma (FOM-CA) undergoing surgical resection and split-thickness skin graft (STSG) reconstruction have not been established. We have performed a cross-sectional QOL analysis of such patients to define functional postoperative outcomes. <b><i>Methods:</i></b> Patients with pathologic stage T1/T2 FOM-CA who underwent resection and STSG re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 33 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…The included studies involved a total of 1849 oral cancer patients of which at least 1308 were male, as one study did not report sex of patients (Vakil et al, 2012 ). Eleven studies only reported mean or median age with SD and did not mention range (Agarwal et al, 2014 ; Bekiroglu et al, 2011 ; Gu et al, 2021 ; Hoene et al, 2021 ; Larson et al, 2021 ; Rogers et al, 2004 ; Rogers & Lowe, 2020 ; Seferin et al, 2022 ; Soares et al, 2018 ; Wu et al, 2020 ; Zhang et al, 2020 ). One study did not mention age of patients (Vakil et al, 2012 ) and three studies categorised patients in age groups without further details about mean and SD (Rogers & Lowe, 2020 ; Yue et al, 2018 ; Zhang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies involved a total of 1849 oral cancer patients of which at least 1308 were male, as one study did not report sex of patients (Vakil et al, 2012 ). Eleven studies only reported mean or median age with SD and did not mention range (Agarwal et al, 2014 ; Bekiroglu et al, 2011 ; Gu et al, 2021 ; Hoene et al, 2021 ; Larson et al, 2021 ; Rogers et al, 2004 ; Rogers & Lowe, 2020 ; Seferin et al, 2022 ; Soares et al, 2018 ; Wu et al, 2020 ; Zhang et al, 2020 ). One study did not mention age of patients (Vakil et al, 2012 ) and three studies categorised patients in age groups without further details about mean and SD (Rogers & Lowe, 2020 ; Yue et al, 2018 ; Zhang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study did not mention age of patients (Vakil et al, 2012 ) and three studies categorised patients in age groups without further details about mean and SD (Rogers & Lowe, 2020 ; Yue et al, 2018 ; Zhang et al, 2020 ). Studies were mainly conducted in China (Fang et al, 2014 ; Fang et al, 2013 ; Gu et al, 2021 ; Li et al, 2013 ; X. Li, Sun, & Guo, 2016 ; W. Li, Zhang et al, 2016 ; Wu et al, 2020 ; Yan et al, 2017 ; Yang et al, 2014 ; Yuan et al, 2016 ; Yue et al, 2018 ; Zhang et al, 2020 ; Zhang et al, 2013 ), followed by India (Agarwal et al, 2014 ; Ghai et al, 2021 ; Sakthivel et al, 2017 ; Vora et al, 2017 ), the United Kingdom (Bekiroglu et al, 2011 ; Devine et al, 2001 ; Rogers et al, 2004 ; Rogers & Lowe, 2020 ), Brazil (Seferin et al, 2022 ; Soares et al, 2018 ), the United States (Larson et al, 2021 ; Ochoa et al, 2021 ), Germany (Hoene et al, 2021 ) and Pakistan (Vakil et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations